SWI versus T2*GRE for ARIA-H monitoring: a pragmatic perspective on adoption in clinical practice - Meike W. Vernooij; Tiago Gil Oliveira; Roland Wiest; Nick C. Fox; Giovanni B. Frisoni; Frederik Barkhof (Neuroradiology, 2026)
Abstract Although radiological severity thresholds for amyloid-related imaging abnormalities with hemosiderin deposition (ARIA-H) were developed using 2-dimensional acquisitions of T2*-weighted gradient-recalled echo (T2*GRE) MRI in pivotal anti-amyloid trials, adoption of well established 3D susceptibility-weighted imaging (SWI) in ARIA-H monitoring in clinical practice represents a reasonable long-term direction for clinical practice. SWI provides documented higher sensitivity and comparable or superior inter-rater reliability compared with conventional T2*GRE for detecting cerebral microbleeds and cortical superficial siderosis, the two key imaging manifestations of ARIA-H. Moreover, SWI is already incorporated into most contemporary dementia MRI protocols, offering important practical and logistical advantages. Available preliminary evidence suggests that the downstream clinical impact of detecting a few additional microbleeds or areas of siderosis may remain modest for most patients. Earlier and more reliable detection could potentially enhance safety by identifying individuals at higher risk of ARIA-H before treatment initiation. The critical requirements are transparency regarding sequence choice and consistency within individual patients over time.